Signifikansi dan Kontribusi Guru Pendidikan Agama Islam dalam Pembentukan Karakter Siswa di Lingkungan Sekolah - Mukhlis Mukhlis (PT Barkah Ilmi Fiddunya, 2024)
This study discusses the significant role of Islamic religious education teachers in shaping students' character within the school environment. Teachers are not only responsible for delivering the curriculum but also serve as role models and motivators for students. Through a holistic approach, teachers can integrate religious values into students' daily lives, thereby fostering the development of positive attitudes, ethics, and morals. This research aims to identify the strategies employed by teachers in educating students and the impact of these strategies on their character development